Performative and Multimedia Aspects of Late-Renaissance Meditative Alchemy: The Case of Michael Maier’s Atalanta Fugiens (1617). - Johann F. W. Hasler. (Revista de Estudios Sociales, 2011)
In 1617 the alchemist, counselor and court physician to the then recently deceased Holy Roman Emperor Rudolf II (1552-1612) published his Atalanta Fugiens (Atalanta feeing). The book fits into the general category of an ‘alchemical emblem book’, very popular in the day: it contains 50 beautiful engravings to which are assigned poetic sextets in both Latin and German. The main difference with all known similar works is that it includes a three-part canon with each engraving. According to the author, the purpose is for all of this input “to be looked at, read, meditated, understood, weighed, sung and listened to, not without a certain pleasure” (Maier 1990, 91). In this sense, this book might be interpreted as a very early example of multimedia, and as a work which requires a performative attitude and activity (in the form of singing) and not merely to be read, for its original purpose to be fully accomplished. In this brief article I will describe the work, and present arguments to support my belief that it would be reasonable to conclude that it is an early form of multimedia.